In vitro effects of triamcinolone acetonide and in combination with hyaluronan on canine normal and spontaneous osteoarthritis articular cartilage - Euppayo T. (2017)
© 2016, The Society for In Vitro Biology. The purposes of this study were to examine the cartilage degradation effects of triamcinolone acetonide (TA) on normal and osteoarthritic ( OA) primary canine chondrocytes and cartilage explants and to examine the cartilage degradation effects of TA in combination with low-molecular-weight hyaluronan (LMWHA). To assess the effects of these drugs on cell culture, 3,[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay and real-time PCR were used to measure chondrotoxicity and determine gene expression, respectively. Uronic acid and hydroxyproline remaining in cartilage and histopathology were used to estimate the effects of these drugs on cartilage explants. In chondrocyte cultures, TA reduced chondrocyte viability in a concentration-dependent manner. LMWHA 2.5 mg/ml combined with TA at IC 20 (0.09 mg/ml) could increase the viability of normal chondrocytes when compared with TA-treated alone. TA at IC 20 induced down-regulation of ACAN and induced up-regulation of ADAMTS5 in canine normal chondrocytes. TA at IC 20 (0.11 mg/ml) up-regulated ADAMTS5, MMP2, MMP3, MMP13, and ACAN expression in canine OA chondrocytes. In explant culture, TA at 1.25, 2.5, and 5 mg/ml increased the severity of structural damage, chondrocyte loss and cluster formation, and proteoglycan loss in OA cartilage. LMWHA could decrease the chondrotoxicity of TA at IC 20 only in normal chondrocytes, as observed by chondrocyte viability. The combination of LMWHA and TA did not show clearly beneficial effects in all other normal and OA samples. Consequently, using TA alone or in combination with LMWHA in OA cartilage should be of concern because it may lead to cartilage destruction.